O corpo, o pensamento e a palavra na poesia de Arnaldo Antunes - Santos, Marina Valesquino Affonso dos (2018)
The poems of Arnaldo Antunes exist as a set of words defined in which the graphical fixations of the language receive contours in the extension of the paper, they are drawn on the screen of the computer, in the video animation and are constantly retaken and redesigned in strong performative bond. The presence of the body is part of the thematic itinerary of the poet and receives categorical dimensions that contribute to the spatial existence concentrating in accommodations that escape the simple blink of a single support. The panorama of these poetic attitudes is present in the book Como é que se chama o nome disso: antologia, published in 2006, by Publifolha. The collection of poems, song lyrics, essays, calligraphy, interviews and a part of unpublished ones welcome a reality committed to the course of the artist's procedures that prioritizes both the act of writing and the possibility of projecting itself into expressions that are rewritten in readings on other platforms. The common place that holds attention to the poems of Arnaldo Antunes lies in a dynamics that occupies rationally the observation without, however, vacate its introspective complexity. The lines drawn, the design of the body of the poem, the body of the person-artist in performance attitude, involve an imbricated universe that protects the vocable, amplifies the noun, nouns the verb and verbalizes the noun: it is the things that are there – in consciousness, in communication, in doing, in existence – with autonomy and which are governed as points of concentration, as organisms that demarcate the instrumental philosophical, artistic and literary structure in all its corporeality. The word: safe harbor for the poet, a minimum unit that allows him to venture into other languages, a source that originated from the interaction between men, character responsible for descriptions of the results of scientific activities, is pondered on its uses by the pre-Socratic philosophers, by the Semiology of Ferdinand de Saussure and Roland Barthes, by the Semiotics of Charles S. Pierce, by the tonal consideration of the voice during the performance act developed by Paul Zumthor, concentrates in some key points of the Contemporary Philosophy and finds the central axis, intentional, moving from this study: sense, sensible and sensitivity, inherent in the poetry of Arnaldo Antunes, seen from the phenomenological optics of Maurice Merleau-Ponty, which unfolds as a touch of poeticity, as a trace of images and with the world perceived according to sensation-perception-knowledge.